STATs in NK-Cells: The Good, the Bad, and the Ugly - Gotthardt, Dagmar; Sexl, Veronika (Frontiers in Immunology, 2017)
NK-cells are major players in the fight against viral infections and transformed cells, but there is increasing evidence attributing a disease-promoting role to NK-cells. Cytokines present in the tumor microenvironment shape NK-cell maturation, function and effector responses. Many cytokines signal via the JAK-STAT pathway that is also frequently altered and constitutively active in a broad range of tumor cells. As a consequence, there are currently major efforts to develop therapeutic strategies to target this pathway. It is therefore of utmost importance to understand the role and contributions of JAK-STAT molecules in NK-cell biology - only this knowledge will allow us to predict effects of JAK-STAT inhibition for NK-cell functions and to successfully apply precision medicine. We will review the current knowledge on the role of JAK-STAT signaling for NK-cell functions and discuss conditions involved in the switch from NK-cell tumor surveillance to disease promotion.